Advances in targeted therapy for acute myeloid leukaemia. (28th November 2017) - Kayser, Sabine; Levis, Mark J.
Summary: In the past few years, research in the underlying pathogenic mechanisms of acute myeloid leukaemia (AML) has led to remarkable advances in our understanding of the disease. Cytogenetic and molecular aberrations are the most important factors in determining response to chemotherapy as well as long‐term outcome, but beyond prognostication are potential therapeutic targets. Our increased understanding of the pathogenesis of AML, facilitated by next‐generation sequencing, has spurred the development of new compounds in the treatment of AML, particularly the creation of small molecules that target the disease on a molecular level. Various new agents, such as tyrosine kinase inhibitors, immune checkpoint inhibitors, monoclonal or bispecific T‐cell engager antibodies, metabolic and pro‐apoptotic agents are currently investigated within clinical trials. The highest response rates are often achieved when new molecularly targeted therapies are combined with standard chemotherapy. Presented here is an overview of novel therapies currently being evaluated in AML.